Faktor Kunci Keberhasilan Usaha Mikro Kecil Dan Menengah (Umkm) Berbasis Ekonomi Kreatif( Studi Kasus Pada Umkm Di Cangwit Creative Space ) - Wijanarko, Aris; , Ihwan Susila, SE., M.Si., Ph.D (2016)
ABSTRACT The purpose of this study to explore the key factors of success of creative effort especially on micro, small, and medium enterprises. The findings of this study are very important in the development of creative business today and in the future. This study used a qualitative approach with case study method. The research data obtained through interviews with five entrepreneurs of micro, small and medium enterprises (SMEs) who opened his business in creative Cangwit Creative Space in Surakarta. Semi-structured interviews conducted at the place of business to ask their business development and the factors that they consider to determine the success of the business. Interviews were recorded, transcribed, and analyzed using the theme (thematic analysis) to obtain the themes and sub-themes that describe the determinants of success of creative effort. The study found that there are four critical success factors of creative SMEs in Surakarta, namely promotion, branding (branding), interest in entrepreneurship and business networks. The results of this study provide a benchmark for similar business that wants to succeed in developing a business. Keywords: case study, creative MSMEs, success factors